The Effect of Platelet-Rich Plasma on Endothelial Progenitor Cell Functionality. (September 2021) - Sidiropoulou, Sofia; Papadaki, Styliani; Tsouka, Aikaterini N.; Koutsaliaris, Ioannis K.; Chantzichristos, Vasileios G.; Pantazi, Despoina; Paschopoulos, Minas E.; Hansson, Kenny M.; Tselepis, Alexandros D.
Platelets mediate circulating endothelial progenitor cell (EPC) recruitment and maturation, participating in vascular repair, however the underlying mechanism(s) remain unclear. We investigated the effect of platelet-rich plasma (PRP) on the functionality of CD34 + -derived late-outgrowth endothelial cells (OECs) in culture. Confluent OECs were coincubated with PRP under platelet aggregation (with adenosine diphosphate; ADP) and nonaggregation conditions, in the presence/absence of the reversible P2Y12 platelet receptor antagonist ticagrelor. Outgrowth endothelial cell activation was evaluated by determining prostacyclin (PGI2 ) and monocyte chemoattractant protein-1 (MCP-1) release and intercellular adhesion molecule-1 (ICAM-1) membrane expression. Similar experiments were performed using human umbilical vein endothelial cells (HUVECs). Platelet-rich plasma increased ICAM-1 expression and PGI2 and MCP-1 secretion compared with autologous platelet-poor plasma, whereas ADP-aggregated platelets in PRP did not exhibit any effect. Platelet-rich plasma pretreated with ticagrelor prior to activation with ADP increased all markers to a similar extent as PRP. Similar results were obtained using HUVECs. In conclusion, PRP induces OEC activation, a phenomenon not observed when platelets are aggregated with ADP. Platelet inhibition with ticagrelor restores the PRP capability to activate OECs. Since EPC activation is important for endothelial regeneration and angiogenesis, we suggest that agents inhibiting platelet aggregation, such as ticagrelor, may promote platelet-EPC interaction and EPC function.